Long-Term Tracking of the Effects of Colostrum-Derived Lacticaseibacillus rhamnosus Probio-M9 on Gut Microbiota in Mice with Colitis-Associated Tumorigenesis - Feiyan Zhao; Keizo Hiraishi; Xiaodong Li; Yaopeng Hu; Daibo Kojima; Zhihong Sun; Heping Zhang; Lin-Hai Kurahara (Biomedicines, 2024)
Intestinal bacteria play important roles in the progression of colitis-associated carcinogenesis. Colostrum-derived Lacticaseibacillus rhamnosus Probio-M9 (Probio-M9) has shown a protective effect in a colitis-associated cancer (CAC) model, but detailed metagenomic analysis had not been performed. Here, we investigated the preventive effects of the probiotic Probio-M9 on CAC-model mice, tracking the microbiota. Feces were obtained at four time points for evaluation of gut microbiota. The effect of Probio-M9 on tight junction protein expression was evaluated in co-cultured Caco-2 cells. Probio-M9 treatment decreased the number of tumors as well as stool consistency score, spleen weight, inflammatory score, and macrophage expression in the CAC model. Probio-M9 accelerated the recovery of the structure, composition, and function of the intestinal microbiota destroyed by azoxymethane (AOM)/dextran sulfate sodium (DSS) by regulating key bacteria (including Lactobacillus murinus, Muribaculaceae bacterium DSM 103720, Muribaculum intestinale, and Lachnospiraceae bacterium A4) and pathways from immediately after administration until the end of the experiment. Probio-M9 co-culture protected against lipopolysaccharide-induced impairment of tight junctions in Caco-2 cells. This study provides valuable insight into the role of Probio-M9 in correcting gut microbiota defects associated with inflammatory bowel disease carcinogenesis and may have clinical application in the treatment of inflammatory carcinogenesis.